Sea cucumbers can enhance coral growth and photophysiological performance under field conditions - Cody S. Clements; Mark E. Hay (Coral Reefs, 2026)
Detritivorous sea cucumbers are important processors of reef sediments and have been hypothesized to enhance coral growth by altering local nutrient availability and seawater chemistry, but whether these effects translate into improved coral performance remains untested. We conducted two analogous field experiments in Mo’orea, French Polynesia, to test whether the sea cucumber Holothuria atra enhances coral growth or photosynthetic efficiency. In the first experiment, we enclosed Acropora pulchra with zero versus two sea cucumbers per 0.25 m 2 , approximating natural densities at our site, and found no detectable effect of sea cucumber presence on growth. In 2025, using densities of four per 0.25 m 2 and enclosing three coral species, A. pulchra growth was 41% greater and Pocillopora verrucosa growth was 17% greater in cages with versus without sea cucumbers. The photosynthetic efficiency of Pocillopora verrucosa was also increased, but that of A. pulchra was not. Porites rus showed no significant response for either metric. Thus, sea cucumbers can enhance coral growth and photophysiological performance under field conditions, but these benefits vary across species, response variables, and apparently sea cucumber density. As sea cucumbers have been widely depleted from tropical reefs, identifying the mechanisms and density thresholds governing these effects will be important for understanding the ecological consequences of their loss and their potential role in supporting coral reef stability or recovery.

Historic coral disturbance versus current coral restoration: insights from Palmyra Atoll - Cody S. Clements; Noam T. Altman-Kurosaki; F. Joseph Pollock; Mark E. Hay (Coral Reefs, 2026)
The utility of passive vs. active coral restoration continues to be debated as reefs decline worldwide. Here, we evaluated the efficacy of coral transplantation into the degraded East and Center lagoons of Palmyra Atoll. Corals have failed to recover in these sites over the eight decades since disturbances associated with World War II, despite high coral cover elsewhere around the atoll that could theoretically provide source propagules. We explicitly compared (i) species beginning to recolonize the lagoons with species common elsewhere at Palmyra, (ii) performance between the East and Center lagoons, and (iii) coral growth at sites near vs. far from causeway inlets as a proxy for the benefits of flow. We found that six common coral species were all physiologically capable of growing in the lagoon, but there were: i) large among-species difference in survival, ii) less, but still significant, differences in growth among species, and iii) localized differences in growth and survival across the eight test locations. Many of these differences appeared to be driven by patterns in fish predation on corals. Survival was greatest for Porites and Pavona species, neither of which have substantially colonized the lagoons. Their superior performance relative to Acropora and Pocillopora species that have begun to recolonize the East Lagoon suggests that transplantation of hardier Porites and Pavona species may accelerate recovery. Coral reef restoration efforts often focus on more threatened and fragile corals like Acropora and Pocillopora . Prioritizing the initial planting of hardier corals like Porites and Pavona may help establish foundational reef functions before introducing more fragile species.

Herbarium Specimens Reveal Long‐Term Decline in Pollination Services Since the 1970s - Bofeng Song; Heidi Zimmer; Mark Clements; Demetra Rakosy; Tiffany M. Knight; Joanne M. Bennett (Global Change Biology, 2026)
Anthropogenic change has resulted in pollinator declines and altered plant–pollinator interactions. This may alter pollination services, reducing the reproductive success of plants. Yet few datasets allow us to track changes in pollination services over time. Herbaria provide a unique opportunity to assess pollination services across broad spatial and temporal scales enabling the examination of associated spatiotemporal anthropogenic drivers of change. We quantified changes in pollination services to the orchid genus Caladenia over the past century, a period of rapid land‐use intensification and climate change in Australia. Examining 10,494 Caladenia flowers preserved at the Australian National Herbarium showed a reduction in pollination services totaling > 60% over the whole study period, with rapid declines occurring post 1970. Declines in pollination services occurred across species pollinated by different taxa and with varying threat status. Sexually deceptive species showed more pronounced declines in pollination services than food‐deceptive species, whereas no decline was detected in the self‐compatible species. Land‐use intensity and rising temperatures were significant predictors of changes in pollination service. Our findings provide rare evidence of declines in pollination services and demonstrate the value of herbarium collections in understanding global change.

Exploring the role of ethnicity and culture in shaping greenspace practices: A qualitative study from Bristol, UK - Andrew K. Palmer; Mark Riley; Laurence Jones; Sarah Clement; Karl L. Evans; Beth F.T. Brockett (Landscape and Urban Planning, 2025)

Pharmacokinetics and Pharmacodynamics of Nomlabofusp in Non-clinical Studies of Friedreich’s Ataxia - Flavia De Toni; Vanessa Ragaglia; Devin Schecter; Angela S. Miller; Eric Gonzalez; Erik J. Wagner; Xin Xu; R. Mark Payne; Jean-Nicholas Mess; Matthew G. Baile; Adrienne Clements-Egan; Gopi Shankar (The AAPS Journal, 2025)
Nomlabofusp is a cell penetrant peptide-based recombinant fusion protein designed to enter cells and deliver human frataxin into the mitochondria of adults and children with Friedreich’s ataxia. In this article we present non-clinical studies evaluating the pharmacology of nomlabofusp, including in a murine striated muscle tissue frataxin knockout model of Friedreich’s ataxia. We demonstrate that subcutaneous administration of nomlabofusp distributes in a dose-dependent manner to several organs including the dorsal root ganglion, heart, and skeletal muscle, which are known to be predominantly affected in Friedreich’s ataxia, as well as to other tissues, including skin. Plasma nomlabofusp concentrations correlated with levels of human frataxin delivered by nomlabofusp into tissues, and the increases in frataxin were correlated amongst tissues, especially with skin. In the knockout mice, we show that the pharmacokinetics and processing of nomlabofusp were comparable with wild type animals and that treatment with nomlabofusp halts the progression of cardiac dysfunction and significantly increased survival. Together, the findings from these non-clinical studies demonstrate that nomlabofusp exposure increases human frataxin in Friedreich’s ataxia-relevant tissues and provide evidence of pharmacologic effects. Graphical Abstract

Biodiversity of macroalgae does not differentially suppress coral performance: The other side of a biodiversity issue - Cody S. Clements; Zoe A. Pratte; Frank J. Stewart; Mark E. Hay (Ecology, 2024)
Hundreds of studies now document positive relationships between biodiversity and critical ecosystem processes, but as ecological communities worldwide shift toward new species configurations, less is known regarding how the biodiversity of undesirable species will shape the functioning of ecosystems or foundation species. We manipulated macroalgal species richness in experimental field plots to test whether and how the identity and diversity of competing macroalgae affected the growth, survival, and microbiome of a common coral in Mo'orea, French Polynesia. Compared to controls without algal competitors, coral growth was significantly suppressed across three macroalgal monocultures, a polyculture of the same three macroalgae, and plots containing inert seaweed mimics; coral mortality was limited and did not differ significantly among treatments. One macroalga suppressed coral growth significantly less than the other two, but none differed from the inert mimic in terms of coral suppression. The composition, dispersion, and diversity of coral microbiomes in treatments with live macroalgae or inert plastic mimics did not differ from controls experiencing no competition. Microbiome composition differed between two macroalgal monocultures and a monoculture versus plastic mimics, but no other microbiome differences were observed among macroalgal or mimic treatments. Together, these findings suggest that algal diversity does not alter harmful impacts of macroalgae on coral performance, which could be accounted for by physical structure alone in these field experiments. While enhancing biodiversity is a recognized strategy for promoting desirable species, it would be worrisome if biodiversity also enhanced the negative impacts of undesirable species. We documented no such effects in this investigation.

Impacts of climate change on mangrove subsistence fisheries: a global review - Roann P. Alberto; Judith A. Teano; Annie Melinda Paz-Alberto; Mark Anthony B. Tangonan; Hazel Jade E. Villamar; Sarah Clement; David J. S. Montagnes; Andrew P. Morse (Marine Life Science & Technology, 2024)
Climate change will impact coastal ecosystems, threatening subsistence fisheries including those in mangrove forests. Despite their global contributions and roles in nutrition and cultural identity, mangrove subsistence fisheries are poorly studied. Here, we offer a foundation for improving the management of mangrove subsistence fisheries to deal with the impending effects of climate change. This multidisciplinary review—drawing on organismal biology, ecology, fisheries, and social science—focuses on the climate impacts relevant to mangrove ecosystems: heat waves, low-category, and high-category typhoons. First, we provide an overview of the mangroves, their harvestable stocks (fish, crustaceans, molluscs), and the fishers, offering an understanding of how they may be affected by relevant environmental variables; i.e., shifts in temperature, salinity, oxygen, flooding, and sediments. Then, we examine the potential effects of climate change on mangrove stocks and fishers, indicating the scope of impending changes. By combining the above information, we develop a simple model that forecasts the number of “fishing-days” lost by fishers due to climate change over the next decade (between 11 and 21 days will be lost per year per fisher). This indicates which aspects of climate change will have the greatest impacts on stocks and fishers. We found that high-category typhoons had more impacts than heat waves, which in turn had a greater impact than low-category typhoons). Finally, recognising gaps in our knowledge and understanding, we offer recommendations for approaches for future work to improve our predictions.

CamTrapAsia : A dataset of tropical forest vertebrate communities from 239 camera trapping studies - Calebe P. Mendes; Wido R. Albert; Zachary Amir; Marc Ancrenaz; Eric Ash; Badrul Azhar; Henry Bernard; Jedediah Brodie; Tom Bruce; Elliot Carr; Gopalasamy Reuben Clements; Glyn Davies; et al. (Ecology, 2024)
Information on tropical Asian vertebrates has traditionally been sparse, particularly when it comes to cryptic species inhabiting the dense forests of the region. Vertebrate populations are declining globally due to land‐use change and hunting, the latter frequently referred as “defaunation.” This is especially true in tropical Asia where there is extensive land‐use change and high human densities. Robust monitoring requires that large volumes of vertebrate population data be made available for use by the scientific and applied communities. Camera traps have emerged as an effective, non‐invasive, widespread, and common approach to surveying vertebrates in their natural habitats. However, camera‐derived datasets remain scattered across a wide array of sources, including published scientific literature, gray literature, and unpublished works, making it challenging for researchers to harness the full potential of cameras for ecology, conservation, and management. In response, we collated and standardized observations from 239 camera trap studies conducted in tropical Asia. There were 278,260 independent records of 371 distinct species, comprising 232 mammals, 132 birds, and seven reptiles. The total trapping effort accumulated in this data paper consisted of 876,606 trap nights, distributed among Indonesia, Singapore, Malaysia, Bhutan, Thailand, Myanmar, Cambodia, Laos, Vietnam, Nepal, and far eastern India. The relatively standardized deployment methods in the region provide a consistent, reliable, and rich count data set relative to other large‐scale pressence‐only data sets, such as the Global Biodiversity Information Facility (GBIF) or citizen science repositories (e.g., iNaturalist), and is thus most similar to eBird. To facilitate the use of these data, we also provide mammalian species trait information and 13 environmental covariates calculated at three spatial scales around the camera survey centroids (within 10‐, 20‐, and 30‐km buffers). We will update the dataset to include broader coverage of temperate Asia and add newer surveys and covariates as they become available. This dataset unlocks immense opportunities for single‐species ecological or conservation studies as well as applied ecology, community ecology, and macroecology investigations. The data are fully available to the public for utilization and research. Please cite this data paper when utilizing the data.

Polyhydroxyalkanoate production in a biofilm by mixed culture phototrophic bacteria - Tim Hülsen; Daniel Venturato; Clement Chan; Luigi Vandi; Bronwyn Laycock; Steven Pratt; Samuel Stegman; Mark van Loosdrecht; Damien J. Batstone (Journal of Cleaner Production, 2024)

Climate and irrigation scenario analyses using three-dimensional numerical modelling: a case study of the Nasia sub-basin in the White Volta Basin, Ghana - Millicent Addai Obeng; Obed Fiifi Fynn; Yvonne Sena Akosua Loh; Larry-Pax Chegbeleh; Clement Alo; Sandow Mark Yidana (Hydrogeology Journal, 2023)

Variance of coral anti-pathogen defense in response to transplantation between coral- and macroalgal-dominated reefs - Deanna S. Beatty; Cody S. Clements; Jinu Mathew Valayil; Simone Y. Jarvis; Kim B. Ritchie; Frank J. Stewart; Mark E. Hay (Coral Reefs, 2022)

Did the historic overharvesting of sea cucumbers make coral more susceptible to pathogens? - Natalie Grayson; Cody S. Clements; Alexandra A. Towner; Deanna S. Beatty; Mark E. Hay (Coral Reefs, 2022)

Anti-drug Antibody Validation Testing and Reporting Harmonization - Heather Myler; João Pedras-Vasconcelos; Kelli Phillips; Charles Scott Hottenstein; Paul Chamberlain; Viswanath Devanaryan; Carol Gleason; Joanne Goodman; Marta Starcevic Manning; Shobha Purushothama; Susan Richards; Honglue Shen; et al. (The AAPS Journal, 2022)
Evolving immunogenicity assay performance expectations and a lack of harmonized anti-drug antibody validation testing and reporting tools have resulted in significant time spent by health authorities and sponsors on resolving filing queries. Following debate at the American Association of Pharmaceutical Sciences National Biotechnology Conference, a group was formed to address these gaps. Over the last 3 years, 44 members from 29 organizations (including 5 members from Europe and 10 members from FDA) discussed gaps in understanding immunogenicity assay requirements and have developed harmonization tools for use by industry scientists to facilitate filings to health authorities. Herein, this team provides testing and reporting strategies and tools for the following assessments: (1) pre-study validation cut point; (2) in-study cut points, including procedures for applying cut points to mixed populations; (3) system suitability control criteria for in-study plate acceptance; (4) assay sensitivity, including the selection of an appropriate low positive control; (5) specificity, including drug and target tolerance; (6) sample stability that reflects sample storage and handling conditions; (7) assay selectivity to matrix components, including hemolytic, lipemic, and disease state matrices; (8) domain specificity for multi-domain therapeutics; (9) and minimum required dilution and extraction-based sample processing for titer reporting. Graphical Abstract

Conservation in the face of hybridisation: genome-wide study to evaluate taxonomic delimitation and conservation status of a threatened orchid species - Natascha D. Wagner; Mark A. Clements; Lalita Simpson; Katharina Nargar (Conservation Genetics, 2021)

Predicting biodiversity richness in rapidly changing landscapes: climate, low human pressure or protection as salvation? - David W. Macdonald; Luca Chiaverini; Helen M. Bothwell; Żaneta Kaszta; Eric Ash; Gilmoore Bolongon; Özgün Emre Can; Ahimsa Campos-Arceiz; Phan Channa; Gopalasamy Reuben Clements; Andrew J. Hearn; Laurie Hedges; et al. (Biodiversity and Conservation, 2020)
Rates of biodiversity loss in Southeast Asia are among the highest in the world, and the Indo-Burma and South-Central China Biodiversity Hotspots rank among the world’s most threatened. Developing robust multi-species conservation models is critical for stemming biodiversity loss both here and globally. We used a large and geographically extensive remote-camera survey and multi-scale, multivariate optimization species distribution modelling to investigate the factors driving biodiversity across these two adjoining biodiversity hotspots. Four major findings emerged from the work. (i) We identified clear spatial patterns of species richness, with two main biodiverse centres in the Thai-Malay Peninsula and in the mountainous region of Southwest China. (ii) Carnivores in particular, and large ungulates to a lesser degree, were the strongest indicators of species richness. (iii) Climate had the largest effect on biodiversity, followed by protected status and human footprint. (iv) Gap analysis between the biodiversity model and the current system of protected areas revealed that the majority of areas supporting the highest predicted biodiversity are not protected. Our results highlighted several key locations that should be prioritized for expanding the protected area network to maximize conservation effectiveness. We demonstrated the importance of switching from single-species to multi-species approaches to highlight areas of high priority for biodiversity conservation. In addition, since these areas mostly occur over multiple countries, we also advocate for a paradigmatic focus on transboundary conservation planning.

Synchronous biological feedbacks in parrotfishes associated with pantropical coral bleaching - Brett M. Taylor; Cassandra E. Benkwitt; Howard Choat; Kendall D. Clements; Nicholas A. J. Graham; Mark G. Meekan (Global Change Biology, 2020)
Biological feedbacks generated through patterns of disturbance are vital for sustaining ecosystem states. Recent ocean warming and thermal anomalies have caused pantropical episodes of coral bleaching, which has led to widespread coral mortality and a range of subsequent effects on coral reef communities. Although the response of many reef‐associated fishes to major disturbance events on coral reefs is negative (e.g., reduced abundance and condition), parrotfishes show strong feedbacks after disturbance to living reef structure manifesting as increases in abundance. However, the mechanisms underlying this response are poorly understood. Using biochronological reconstructions of annual otolith (ear stone) growth from two ocean basins, we tested whether parrotfish growth was enhanced following bleaching‐related coral mortality, thus providing an organismal mechanism for demographic changes in populations. Both major feeding guilds of parrotfishes (scrapers and excavators) exhibited enhanced growth of individuals after bleaching that was decoupled from expected thermal performance, a pattern that was not evident in other reef fish taxa from the same environment. These results provide evidence for a more nuanced ecological feedback system—one where disturbance plays a key role in mediating parrotfish–benthos interactions. By influencing the biology of assemblages, disturbance can thereby stimulate change in parrotfish grazing intensity and ultimately reef geomorphology over time. This feedback cycle operated historically at within‐reef scales; however, our results demonstrate that the scale, magnitude, and severity of recent thermal events are entraining the biological responses of disparate communities to respond in synchrony. This may fundamentally alter feedbacks in the relationships between parrotfishes and reef systems.

Integrated Observations of Global Surface Winds, Currents, and Waves: Requirements and Challenges for the Next Decade - Ana B. Villas Bôas; Fabrice Ardhuin; Alex Ayet; Mark A. Bourassa; Peter Brandt; Betrand Chapron; Bruce D. Cornuelle; J. T. Farrar; Melanie R. Fewings; Baylor Fox-Kemper; Sarah T. Gille; Christine Gommenginger; et al. (Frontiers in Marine Science, 2019)

Historical forcings as main drivers of the Atlantic multidecadal variability in the CESM large ensemble - Katinka Bellomo; Lisa N. Murphy; Mark A. Cane; Amy C. Clement; Lorenzo M. Polvani (Climate Dynamics, 2018)

Construction of an ultra-high density consensus genetic map, and enhancement of the physical map from genome sequencing in Lupinus angustifolius - Gaofeng Zhou; Jianbo Jian; Penghao Wang; Chengdao Li; Ye Tao; Xuan Li; Daniel Renshaw; Jonathan Clements; Mark Sweetingham; Huaan Yang (Theoretical and Applied Genetics, 2018)

Evidence of the island rule and microevolution in white-footed mice (Peromyscus leucopus) in an urban harbor archipelago - Lauren Nolfo-Clements; Rossano Butcher; Mikayla Leite; Mark Clements (Mammal Research, 2017)

Opsins have evolved under the permanent heterozygote model: insights from phylotranscriptomics of Odonata - Anton Suvorov; Nicholas O. Jensen; Camilla R. Sharkey; M. Stanley Fujimoto; Paul Bodily; Haley M. Cahill Wightman; T. Heath Ogden; Mark J. Clement; Seth M. Bybee (Molecular Ecology, 2017)
Gene duplication plays a central role in adaptation to novel environments by providing new genetic material for functional divergence and evolution of biological complexity. Several evolutionary models have been proposed for gene duplication to explain how new gene copies are preserved by natural selection, but these models have rarely been tested using empirical data. Opsin proteins, when combined with a chromophore, form a photopigment that is responsible for the absorption of light, the first step in the phototransduction cascade. Adaptive gene duplications have occurred many times within the animal opsins’ gene family, leading to novel wavelength sensitivities. Consequently, opsins are an attractive choice for the study of gene duplication evolutionary models. Odonata (dragonflies and damselflies) have the largest opsin repertoire of any insect currently known. Additionally, there is tremendous variation in opsin copy number between species, particularly in the long‐wavelength‐sensitive ( LWS ) class. Using comprehensive phylotranscriptomic and statistical approaches, we tested various evolutionary models of gene duplication. Our results suggest that both the blue‐sensitive ( BS ) and LWS opsin classes were subjected to strong positive selection that greatly weakens after multiple duplication events, a pattern that is consistent with the permanent heterozygote model. Due to the immense interspecific variation and duplicability potential of opsin genes among odonates, they represent a unique model system to test hypotheses regarding opsin gene duplication and diversification at the molecular level.

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

What a difference a bay makes: natural variation in dietary resources mediates growth in a recently settled herbivorous fish - Mark A. Priest; Andrew R. Halford; Kendall D. Clements; Emily Douglas; Sheena L. Abellana; Jennifer L. McIlwain (Coral Reefs, 2016)

Orchid historical biogeography, diversification, Antarctica and the paradox of orchid dispersal - Thomas J. Givnish; Daniel Spalink; Mercedes Ames; Stephanie P. Lyon; Steven J. Hunter; Alejandro Zuluaga; Alfonso Doucette; Giovanny Giraldo Caro; James McDaniel; Mark A. Clements; Mary T. K. Arroyo; Lorena Endara; et al. (Journal of Biogeography, 2016)
Aim Orchidaceae is the most species‐rich angiosperm family and has one of the broadest distributions. Until now, the lack of a well‐resolved phylogeny has prevented analyses of orchid historical biogeography. In this study, we use such a phylogeny to estimate the geographical spread of orchids, evaluate the importance of different regions in their diversification and assess the role of long‐distance dispersal ( LDD ) in generating orchid diversity. Location Global. Methods Analyses use a phylogeny including species representing all five orchid subfamilies and almost all tribes and subtribes, calibrated against 17 angiosperm fossils. We estimated historical biogeography and assessed the importance of different regions for rates of speciation, extinction and net species diversification. We evaluated the impact of particular LDD events on orchid diversity by asking how many species evolved in the new range subsequent to those events. Results Orchids appear to have arisen in Australia 112 Ma (95% higher probability distribution: 102.0–120.0 Ma), then spread to the Neotropics via Antarctica by 90 Ma ( HPD : 79.7–99.5 Ma), when all three continents were in close contact and apostasioids split from the ancestor of all other orchids. Ancestors of vanilloids, cypripedioids and orchidoids+epidendroids appear to have originated in the Neotropics 84–64 Ma. Repeated long‐ and short‐distance dispersal occurred through orchid history: stochastic mapping identified a mean total of 74 LDD events or 0.8 Ma −1 . Across orchid history, Southeast Asia was the most important source and maximally accelerated net diversification; across epidendroids, the Neotropics maximally accelerated diversification. Main conclusions Our analysis provides the first biogeographical history of the orchids, implicating Australia, the Neotropics and Antarctica in their origin. LDD and life in the Neotropics – especially the Andes – had profound effects on their spread and diversification; > 97% of all orchid species are restricted to individual continents.

Contribution of direct electron transfer mechanisms to overall electron transfer in microbial fuel cells utilising Shewanella oneidensis as biocatalyst - Segun Fapetu; Taj Keshavarz; Mark Clements; Godfrey Kyazze (Biotechnology Letters, 2016)

RHEB1 expression in embryonic and postnatal mouse - Qi Tian; James L. Smart; Joachim H. Clement; Yingming Wang; Alex Derkatch; Harald Schubert; Michael V. Danilchik; Daniel L. Marks; Lev M. Fedorov (Histochemistry and Cell Biology, 2016)

The association of ultraviolet radiation-B (305 nm), season of diagnosis, and latitude on the survival outcome of prostate cancer in the high UV environment of Australia - Visalini Nair-Shalliker; David P. Smith; Sam Egger; Mark S. Clements; Md. Bayzidur Rahman; Bruce K. Armstrong (Cancer Causes & Control, 2013)

Relationship between cancer survival and ambient ultraviolet B irradiance in China - Wanqing Chen; Bruce K. Armstrong; Bayzidur Rahman; Rongshou Zheng; Siwei Zhang; Mark Clements (Cancer Causes & Control, 2013)

Functional mobility of older adults after concentric and eccentric endurance exercise - Mandy Lucinda Gault; Richard Edward Clements; Mark Elizabeth Theodorus Willems (European Journal of Applied Physiology, 2012)

Estimating prevalence of distant metastatic breast cancer: a means of filling a data gap - Mark S. Clements; David M. Roder; Xue Qin Yu; Sam Egger; Dianne L. O’Connell (Cancer Causes & Control, 2012)

Taxonomic and functional diversity of farmland bird communities across Europe: effects of biogeography and agricultural intensification - Irene Guerrero; Manuel B. Morales; Juan J. Oñate; Tsipe Aavik; Jan Bengtsson; Frank Berendse; Lars W. Clement; Christopher Dennis; Sönke Eggers; Mark Emmerson; Christina Fischer; Andreas Flohre; et al. (Biodiversity and Conservation, 2011)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Recent Advances in Arctic Ocean Studies Employing Models from the Arctic Ocean Model Intercomparison Project - Andrey Proshutinsky; Yevgeny Aksenov; Jaclyn Clement Kinney; Rüdiger Gerdes; Elena Golubeva; David Holland; Greg Holloway; Alexandra Jahn; Mark Johnson; Ekaterina Popova; Mike Steele; Eiji Watanabe (Oceanography, 2011)

Relationship between cancer mortality/incidence and ambient ultraviolet B irradiance in China - Wanqing Chen; Mark Clements; Bayzidur Rahman; Siwei Zhang; Youlin Qiao; Bruce K. Armstrong (Cancer Causes & Control, 2010)

Trio under threat: can we secure the future of rhinos, elephants and tigers in Malaysia? - Reuben Clements; Darmaraj Mark Rayan; Abdul Wahab Ahmad Zafir; Arun Venkataraman; Raymond Alfred; Junaidi Payne; Laurentius Ambu; Dionysius Shankar Kumar Sharma (Biodiversity and Conservation, 2010)

Biology and molecular phylogenetics of Nematoceras sulcatum, a second endemic orchid species from subantarctic Macquarie Island - Mark A. Clements; Anne M. Mackenzie; Geof R. Copson; Brian P. J. Molloy; Noel Carmichael; Mary L. Skotnicki; Patricia M. Selkirk (Polar Biology, 2007)

Identification of the endangered Australian orchid Microtis angusii using an allele-specific PCR assay - Nicola S. Flanagan; Rod Peakall; Mark A. Clements; J. Tupac Otero (Conservation Genetics, 2007)

Conservation of taxonomically difficult species: the case of the Australian orchid, Microtis angusii - Nicola S. Flanagan; Rod Peakall; Mark A. Clements; J. Tupac Otero (Conservation Genetics, 2006)

Novel phenotypes identified by plasma biochemical screening in the mouse - Tertius A. Hough; Patrick M. Nolan; Vicky Tsipouri; Ayo A. Toye; Ian C. Gray; Michelle Goldsworthy; Lee Moir; Roger D. Cox; Sian Clements; Peter H. Glenister; John Wood; Rachael L. Selley; et al. (Mammalian Genome, 2002)

Modelling of congenital nystagmus waveforms produced by saccadic system abnormalities - David S. Broomhead; Richard A. Clement; Mark R. Muldoon; Jonathan P. Whittle; Columba Scallan; Richard V. Abadi (Biological Cybernetics, 2000)

A Comparison of the Structures of the Alpha:Beta and Alpha:Gamma Dimers of Mouse Salivary Androgen-Binding Protein (ABP) and Their Differential Steroid Bindin - Robert C. Karn; Mark A. Clements (Biochemical Genetics, 1999)